EMERGENCY REVISITED - Dr.Naveen Vashishta (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
From 1975 to 1977, India saw one of the most controversial times in its post-independence history: the Emergency. The Emergency is revisited in this study article, which also looks at its causes, execution, and long-term effects on Indian politics and society. The Emergency, which was proclaimed by Prime Minister Indira Gandhi at the time, resulted in the widespread incarceration of political opponents, the suspension of civil liberties, and press censorship. The study explores the political and socioeconomic circumstances that preceded the Emergency, as well as the difficulties that Indira Gandhi's administration encountered, including judicial scrutiny, political dissension, and unstable economies. It examines the constitutional and legal justifications used for the Emergency declaration and the later revisions to the Indian Constitution intended to give legitimacy to these measures.